AIDDA'S PERSUASIVE COMMUNICATION IN PREVENTING INTER-SCHOOL STUDENT FIGHTS: A STUDY AT STATE VOCATIONAL HIGH SCHOOL 2 PANGKALPINANG - Rizky Noviar Ramadhan; Septiadi (MEDIOVA: Journal of Islamic Media Studies, 2025)
Changing a person’s thoughts, attitudes, and behaviors is one of the primary goals of communication. The concept involves intellectual aspects, including beliefs, thoughts, and ideas; while attitudes and behaviors are associated with physical factors, including emotions. Persuasive communication is defined as the ability to touch the heart, evoke shared emotions, and foster liking and acceptance of the conveyed ideas. It is essential to communicate objectives clearly in persuasive communication. Communicators face diverse goals and must pay attention to demographic, occupational, ethnic, social, and other contextual factors. This study employed a qualitative research method, with data collected through interviews, observation, and documentation. The data were analyzed using qualitative data analysis techniques. The research findings show that: 1) Persuasive communication is implemented following the AIDDA (Attention, Interest, Desire, Decision, Action) approach. The school has become one of the key instruments in preventing acts of student delinquency. Attention is achieved by providing emotional engagement; Interest is developed through personal approaches that encourage students to participate in positive activities; Desire is fostered by providing positive motivation; Decision involves appointing teachers and students who demonstrate positive behavior as role models, sharing exemplary stories of national heroes and leaders, and organizing mentoring programs by religious scholars and local police to instill positive values that influence students’ decision-making; and Action includes conducting home visits, providing special guidance, and implementing disciplinary measures; 2) The impact includes the school’s use of social and print media as anti-bullying tools by disseminating information about the negative effects of bullying and forming Roots as agents of change within the school. This initiative has fostered a more harmonious school environment, supported by continuous evaluations conducted weekly, monthly, and every semester. As a result, students have become better at managing their emotions, and there have been notable improvements in their attitudes and behaviors, along with a decreasing trend in bullying incidents.